(untitled) (Biocenosis, 2026)
Bird-window collisions cause the death of millions of birds worldwide. This article describes the process of diagnosis, design, development, and response analysis of an educational campaign on bird-window collisions carried out through the Facebook group of the Costa Rican Ornithological Association (AOCR). Beliefs about how to respond when finding a bird injured after hitting a window were identified, and based on the comments, eight educational objectives were defined. The educational campaign consisted of 24 posts and was conducted at the end of 2024. To evaluate the campaign, the engagement rate of each post was calculated, and the comments per post were analyzed. It was concluded that members of the AOCR Facebook group hold both accurate and inaccurate beliefs about how to act in the event of a bird colliding with a window, and that some of the recommended actions may worsen the condition of an injured bird. Campaign messages aimed at debunking misconceptions, and disseminating and promoting effective methods to reduce collisions showed higher engagement rates among group members. The use of social media is recommended for disseminating environmental messages due to its wide reach, lack of economic cost and the possibility of measuring both the reach and the engagement rate of posts, as well as analyzing readers’ comments.